Impact of Legal Regulations on Innovation in Digital Donation Platforms for Youtube Streamers - Agus Wardhono; Wahyu Prawesthi; M Syahrul Borman; Toong Hai Sam; Taffy Faiq Syahmi (Trunojoyo Madura University, 2025)
This study investigates the regulatory implications for the development of digital donation platforms in Indonesia, with a particular focus on Saweria, which is widely utilized by YouTube content creators. The advancement of digital technology has facilitated innovative fundraising through donation-based crowdfunding, yet it simultaneously generates potential risks of misuse. Employing a normative juridical research approach, this study examines the vulnerability of digital donation platforms—initially intended to serve as financial support mechanisms—to exploitation for unlawful purposes, notably the dissemination and promotion of online gambling activities. The findings indicate that although the Information and Electronic Transactions Law (ITE Law), particularly Article 27 paragraph (2) jo. Article 45 as amended by Law No. 1 of 2024, stipulates prohibitions on gambling-related content with sanctions of up to six years imprisonment and/or administrative fines of IDR 1 billion, its enforcement continues to encounter evidentiary and procedural constraints. The study emphasizes the necessity for more specific regulatory frameworks, enhanced platform security, increased awareness among content creators, and coordinated multi-stakeholder collaboration to develop adaptive safeguards against digital criminality.